Pengembangan Media Pembelajaran PAI-BP Berbasis Augmented Reality pada Bab Peran dan Keteladanan Tokoh Ulama Islam di Indonesia - Tuti Alawiyah; Laila Nur Sahwa; Rahmadani Rahmadani; Muhammad Hatta (An-Nuha, 2022)
This study aims to develop an Augmented Reality (AR)-based learning media for Islamic Religious Education and Character (PAI-BP) on the topic Roles and Exemplary Figures of Islamic Scholars in Indonesia for Grade XI students at SMA Negeri 3 Panyabungan. Before the implementation of this media, students were less focused during learning due to the use of textual and less engaging materials. The development model applied in this study is ADDIE (Analysis, Design, Development, Implementation, and Evaluation), using qualitative and quantitative approaches through observation, interviews, documentation, expert validation questionnaires, and limited trials. The research subjects included the PAI-BP teacher, 30 students, and material and media experts. The results showed that the AR-based media was highly valid (91.8%) and practical, receiving positive responses from 90% of teachers and 84.1% of students. The media presents Islamic scholars in 3D visualization, animation, and contextual information accessible via mobile devices using the Essmblr Edu application. The use of AR media effectively increased students’ activeness, interaction, and understanding. Teachers also played a vital role as facilitators during the learning process. Thus, AR- based learning media is considered an effective and relevant innovation to enhance the quality of Islamic Religious Education in the digital era.